Hubungan Dukungan Sosial dan Kecerdasan Emosional dengan Kesejahteraan Psikologis pada Mahasiswa Perantau - Bandi, Elia Febry Herniron; Hernawati, Lucia; Winarno, Alphonsus Rachmad Jati (Jurnal Psikologi TALENTA, 2025)
Psychological well-being is important for migrant students. The influencing factors are social support and emotional intelligence. This study aims to determine the relationship between social support and emotional intelligence with the psychological well-being of migrant students. Participants in this study were 100 migrant students. Measuring tools used are social support scale, emotional intelligence scale, and psychological well-being scale. The research hypothesis is that there is a positive relationship between social support and emotional intelligence with psychological well-being. The method of two-predictor regression analysis is to test the major hypothesis, while the product moment analysis is to test the minor hypothesis. The results showed that there was a positive and very significant relationship between social support and emotional intelligence and psychological well-being in migrant students with an R coefficient of 0,667 and an F of 38,914 with a significance of 0,000 (p<0,01). The effective contribution of the two predictors was 44,5%. There is a positive relationship between social support and psychological well-being for overseas students (rx1y=0,453; sig p<0,01). There is a positive relationship between emotional intelligence and psychological well-being of migrant students (rx2y=0,629; sig p<0,01). This research shows the importance of social support and emotional intelligence to maintain the psychological well-being of migrant students.